Entrepreneurship - Bygrave, William D.; Zacharakis, Andrew (New Jersey : John Wiley & Son, Inc., 2014)
This book combines concepts and cases to present the latest theory theory about entrepreneurship and relate actual experiences.
The power of entrepreneurship -- The entrepreneurial process -- Opportunity recognition, shaping, and reshaping -- Understanding your business model and developing your strategy -- Entrepreneurial marketing -- Building the founding team -- The business planning process -- Building your pro-forma financial statements -- Financing entrepreneurial ventures worldwide -- Raising money for starting and growing businesses -- Debt and other forms of financing -- Legal and tax issues, including intellectual property -- Entrepreneurial growth -- Social entrepreneurship
Includes index.
Keywords: ENTREPRENEURSHIP